PERANCANGAN ENVIRONMENTAL GRAPHIC DESIGN MUSEUM SEPULUH NOPEMBER SURABAYA SEGABAI PENDUKUNG PROGRAM SURABAYA CITY TOUR - Hidayat, Royyan; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The goal of the design of Environmental Graphic Design Museum Ten November Surabaya is as a supporting program of Surabaya City Tour tour. The study was conducted using qualitative research methods is to conduct in-depth understanding of the objects that can be done by observation, interviews, documentation and literature to obtain the data used to support the design of Environmental Graphic Design. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that refer to design communication strategies that will be used to reach the intended target audience. After analyzing the data, found a design concept or keyword of